Adolescent Summer Camp Volunteers' Attitudes Toward Peers with Disabilities. (4th May 2017) - Fort, Megan; Lundberg, Neil; Zabriskie, Ramon; Eggett, Dennis; Prater, Mary Anne; Barney, Keith
ABSTRACT: This study explored the malleability of adolescent attitudes toward their peers with disabilities after volunteering in a summer day-camp. The Contact with Disabled Persons Scale (CDP) and the Multi-Dimensional Attitude Scale (MAS) were used to collect data in order to determine the association between volunteering in a recreation-based summer day camp and adolescent attitudes toward disability. After a covariate-adjusted regression analysis, contact with individuals with disabilities was found to significantly predict change in attitudes toward disability. Dyadic interviews were held after camp participation to provide additional sources of data with potential for deeper understanding of the camp experience for volunteers. The data suggested that participants perceived camp as a setting for the development of relationships with peers who have disabilities. These relationships further framed participants' understanding of the experience as fun, difficult, and resulting in perceived personal change. Implications for future research are discussed.